Dampak Pendemi Covi-D 19 terhadap Pelaksanaan Pembelajaran Baca Tulis Al-Quran di Taman Pendidikan Al Qur’an (TPQ) Kecamatan Sanggau Ledo - Uyung Yuliza; Sri Lestari; Yapandi Yapandi; Rianawati Rianawati (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2021)
The Covid-19 pandemic has caused the implementation of learning in formal and non-formal educational institutions not to run properly. One of the non-formal educational institutions affected by the Covid-19 pandemic is the TPQ. The government’s policy to temporarily suspend the implementation of face-to-face learning in all educational institutions has an impact on the implementation of learning at TPQ. The focus of the problem in this study is 1. How is the impact of the covid 19 pandemic on the implementation of TPQ learning in Sanggau Ledo District. 2. What impact did TPQ have in Sanggau Ledo District during the Covid 19 Pandemic. 3. Did TPQ in Sanggau Ledo District play a role in socializing the Covid 19 Pandemic. The study was conducted in Sanggau Ledo District, Bengkayang Regency. The research approach used is a qualitative approach with case study methods, data processing using triangulation and data analysis using Miles and Huberman model analysis techniques. Sources of information in this study were 6 Head of TPQ in Sanggau Ledo District. The information obtained from the results of this study is that the implementation of learning at TPQ is less effective for TPQs who give their students a day off and is still running effectively for TPQs who continue to carry out face-to-face learning. TPQ institutions, students, teachers and parents of TPQ students feel the impact of this condition. TPQ also plays a role in socializing the Covid-19 pandemic, especially to TPQ students.